Qualitative Insight of Informal Sector’s Wages: In the Case of Home-based Handicraft Workers in Kathmandu Valley - Adhikari, Padma Kumar (Humanities and Social Sciences Journal, 2024)
This study examines the qualitative factors influencing wages among informal sector workers in home-based handicraft occupations in the Kathmandu Valley, utilizing a qualitative regression model and primary data from 426 laborers. The findings reveal that age, education, and daily working hours have a positive influence on wages, whereas workers' experience, family involvement, and job-related risks exert a negative impact. Notably, job satisfaction is strongly correlated with an increase in wages, suggesting that improved working conditions directly affected earnings in the informal sector. Again, evidences of the value of R², D-W statistic, and ANOVA results support policies such as providing quality education and vocational training, improving working conditions, and legal protections for informal workers to promote wage growth and job security. The study can be further elaborated on the effects of educational programs on wage disparities by exploring the role of gender and other demographic factors in this workforce, facing the socioeconomic challenges.